A Study of Measurements of Spinal Canal at the Level of Lower Three Lumbar Vertebra by 16 Slice CT Scanner in Nepalese Population - Mallik, Mukesh; Paudel, Keshav; Subedi, Nuwadatta; Sah, Sanjay; Subedee, Anish; Adhikari, Deepak (Journal of College of Medical Sciences-Nepal, 2015)
Background and Objective: The study was conducted with the objectives to establish the measurements of spinal canal and lumbar vertebra at L3 to L5 region in Nepalese population. Methodology: It is a cross-sectional study among 36 patients (17 males and 19 females) having age variation from 20-60years whose abdomen was scanned by GE bright speed 16 slice CT scanner with slice thickness 10mm and then reconstructed at 1.2mm for images in different body plains for the measurement of spinal canal. Results: Almost all the parameters increase from L3 to L4 to L5 but the difference is more between L4 and L5 than between L3 and L4 except in vertebral body width (VBW) where it increases smoothly, however canal body ratio (CBR) remained constant at 0.6. All the parameters were larger in males than in females except antero-posterior dimension of canal in transverse section (APT) which is larger in females. It also shows that none of the parameters vary significantly depending upon sex except vertebral body width (VBW) at L3 which is 39.041 ± 4.1334 in males and 36.474 ± 2.8509 in females (p=0.036). Conclusion: Antero- posterior dimension in trans-verse and sagittal is almost identical but the chances of measurement error is higher in transverse due to trigonal shape of canal so AP diameter should be done in sagittal section as this is consistent and measures 14mm at L3, 14mm at L4 and 15 mm at L5 hence defining average antero-posterior canal dimension in sagittal section to be 14 mm but CBR constant at 0.6. JCMS Nepal 2014; 10(4):6-11